2022
DOI: 10.3390/land11122158
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Dynamics of Wetlands in Guangdong-Hong Kong-Macao Greater Bay Area from 1976 to 2019

Abstract: Wetland ecosystems contain rich natural resources and vital ecological functions, and the investigation of spatial and temporal evolution characteristics of wetlands and their driving factors is critical for the management and conservation of wetlands. This study aimed to explore the spatial and temporal dynamics of wetlands in the Guangdong–Hong Kong–Macao Greater Bay Area (GBA) from 1976 to 2019 using multi-source remote sensing data (DISP KH-9, Landsat, and GaoFen-1), combing with the object-based classific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Historical spy-satellite data has been successfully used for mapping land cover and, therefore, ecosystem extent, especially of forests (Wardell et al 2003 , Rannow 2013 , Dao Minh et al 2017 ); agriculture (Dao Minh et al 2009 , Munteanu et al 2020 , Rendenieks et al 2020 ); shrub encroachment (Frost and Epstein 2013 ); surface water (Hamandawana 2007 , Shugar et al 2020 , Liu et al 2022 ); and urban expansion (Cetin 2009 ). These studies highlight that historical ecosystem changes sometimes outpaced more recent changes mapped with Landsat-era remote sensing data (Nita et al 2018 , Munteanu et al 2020 ).…”
Section: Recent and Current Applicationsmentioning
confidence: 99%
“…Historical spy-satellite data has been successfully used for mapping land cover and, therefore, ecosystem extent, especially of forests (Wardell et al 2003 , Rannow 2013 , Dao Minh et al 2017 ); agriculture (Dao Minh et al 2009 , Munteanu et al 2020 , Rendenieks et al 2020 ); shrub encroachment (Frost and Epstein 2013 ); surface water (Hamandawana 2007 , Shugar et al 2020 , Liu et al 2022 ); and urban expansion (Cetin 2009 ). These studies highlight that historical ecosystem changes sometimes outpaced more recent changes mapped with Landsat-era remote sensing data (Nita et al 2018 , Munteanu et al 2020 ).…”
Section: Recent and Current Applicationsmentioning
confidence: 99%
“…With the increasing intensity of human activities, pollution is one of the most apparent and persistent threats to mangrove health. High levels of organic wastewater discharged from aquaculture can have adverse effects on mangroves, especially on seedlings (Lu et al, 2022).…”
Section: Pollution and Waste Dischargementioning
confidence: 99%
“…Due to the lack of effective methods to control excessive human activity, the fifth assessment reports from the IPCC (Intergovernmental Panel on Climate Change) predicted further global warming trends, including the temperature rising, a precipitation regime shift, a sea level rise, and an increasing frequency of extreme climate events [33][34][35]. Previous studies have confirmed that the main driving factors for wetlands include precipitation, temperature, elevation, slope, population, and GDP (gross domestic product), which significantly influence the spatial and temporal variations of wetlands [36][37][38]. Therefore, constructing a perfect indicator system of driving factors is the primary issue in wetland variation analysis.…”
Section: Introductionmentioning
confidence: 97%